Dynamics and severity model in managing fungal diseases (The Journal of Plant Protection Sciences, 2020)
A survey was undertaken during 1996-1997 in different commercial perennial ornamentals in gardens and nurseries at Bolpur, Santiniketan and Sriniketan of Birbhum District, West Bengal, India, to study the fungal diseases of some commercial ornamentals. The leaf spot of Ficus religiosa (c.o. Alternaria sp.) is the first record. Fifteen fungal diseases have been formally described from West Bengal for the first time on these twelve ornamentals. Monthly dynamics was determined for occurrence, intensity and severity of these diseases.
Keywords: Commercial ornamentals; indirect assessment of yield loss; post-appearance protection of apprehended loss; new reports; new state records